Making an impact: the new 2024 Medical Library Association research agenda - Marie T. Ascher; Margaret A. Hoogland; Karen M. Heskett; Heather N. Holmes; Jonathan D. Eldredge (Journal of the Medical Library Association)
Objective: This research project sought to identify those subject areas that leaders and researcher members of the Medical Library Association (MLA) determined to be of greatest importance for research investigation. It updates two previous studies conducted in 2008 and 2011.